The Influence of Credit, Risk, and Efficiency on Profitability with Independent Commissioners’ Moderation - Lorentia Handoko; Lutfi, Lutfi; Denpharanto Agung Krisprimandoyo (CV. AFDIFAL MAJU BERKAH, 2026)
This study investigates the determinants of profitability in Indonesia’s Regional Development Banks (BPD) by examining the roles of credit distribution, credit risk, operational efficiency, and the proportion of independent commissioners as a moderating variable. Using panel data from 23 BPDs over the 2013–2023 period and employing a quantitative approach with fixed effect panel regression, the analysis finds that the average ROA of BPDs is 1.84% and ROE is 16.64%, both lower than those of non-BPD banks. Results show that Loan to Deposit Ratio (LDR) has a significant positive effect on ROA (coefficient 0.005557; t-value 2.54), with every 1% increase in LDR raising ROA by 0.0056%. Operational efficiency, as measured by POBO, also positively impacts profitability (coefficient 0.053626; t-value 23.17), while a 1% increase in POBO boosts ROA by 0.054%. Non-Performing Loans (NPL) do not significantly affect ROA, but negatively affect ROE. The proportion of independent commissioners (mean 66.32%) has a significant negative effect on ROA (coefficient –0.003460; t-value –2.68), and does not significantly moderate the LDR-ROA relationship. The models have high explanatory power (R² = 0.9136 for ROA; R² = 0.7767 for ROE). The study concludes that credit distribution and operational efficiency are primary drivers of BPD profitability, but increasing independent commissioners may reduce ROA. It is recommended that BPDs optimize lending, improve efficiency, and refine governance for sustainable performance.